FRI0224 Lymphoproliferative disorders in primary sjÖgren's syndrome: a ten years follow-up study of 68 cases. (1st June 2001) - Botsios, C; Sfriso, P; Semerano, L; Ostuni, P; Grava, C; Gambari, PF
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease chiefly involving salivary and lachrymal glands, associated with a high risk of developing non Hodgkin's lymphoma (NHL) (about 44 times higher than in the general population), usually B-cell lymphomas of mucosa associated lymphoid tissue (MALT). Anyway, the most frequent histologic lesion of major salivary glands of pSS patients is myoephitelial sialadenitis (MESA). Objectives: We longitudinally studied the prevalence and the clinical features of lymphoproliferative disorders in a large cohort of pSS patients throughout a 10-years follow-up period. Methods: We evaluated 68 consecutive outpatients, affected by pSS according to the Fox's criteria, followed since January 1987 to November 2000. Patients were divided into two groups, according to their autoantibodies pattern at the time of diagnosis: anti-Ro and/or La positive vs anti-Ro/La negative. We excluded patients affected either by secondary SS or associated to other connective tissue diseases and HCV infection, or by isolated keratoconjunctivitis sicca and those taking drugs causing sicca syndrome. We even calculated the relative risk on the basis of incidence rate of NHL as reported by Italian Cancer Registry. Results: Lymphoproliferative disorders were diagnosed in 5 (7.35%) patients. Lymphoproliferation was significantly prevalent in the Ro/La positive group (p = 0.041). We recorded 2 cases of NHL of intermediate or low grade malignancy (1 rhinofaringeal plasmocytoma associated with glomerulonephritis and monoclonal crioglobulinemia and 1 parotid MALToma) and 3 pre-neoplastic disorders (2 cases of MESA and 1 case of renal lymphoproliferative disorder). The latter died of melanoma 4 years after the diagnosis of lymphoproliferative disorder. In all the cases the development of a lymphoproliferative disorder was associated with purpura, parotid swelling and low C4 levels, either at the time of diagnosis or during the follow-up. Kaplan-Meier rates analyses showed that MESA and NHL represented late occurring events in the course of pSS. According to our results, the relative risk (RR) to develop NHL was 36.1 for the whole group with pSS (p < 0.001), while for the Ro and/or La positive group was 47.1. Ten years survivorship in pSS patients was not significantly lower with respect to the general population (86.5 vs 90%) calculated with the aid of life tables of the Italian general population (matched for age and sex). Conclusion: Patients with purpura, parotid swelling, low C4 levels and cryoglobulinemia present an increased risk to develop lymphoproliferative disorders. These clinical and laboratory findings seem to identify a subgroup of patients with pSS which should be controlled and, maybe, treated in a different way.